Konkretisierung des Komplementaritatsprinzips des Internationalen Strafgerichtshofs - Tharakan, Steve (Zurich Dike, 2009)
In recent years, public international law has become a matter of general interest. It has become part of the world of real (power) politics and its principles have become ingrained in the way everyday people formulate their thoughts. The author of this book makes public international law comprehensible by approaching it from various perspectives. He deliberately goes beyond the restricted circle of international law specialists. This can be seen in the method underlying his work. In addition to academic studies, which repeatedly demonstrate unconventional aspects, there are also sections that are easily accessible for everybody. Even the casual reader is catered to, due to the brevity of the texts, which are largely self-contained. One can pick up and start reading the book at any point. A large number of subjects are examined, spanning such topics as war and neutrality, people's right of self determination, the protection of minorities and other human rights, and international humanit
- Einleitung
- Kapitel 1: komplementaritatsbegriff
- Kapitel 2: zur auslegung des rom- statuts
- Kapital 3: Gerichtsbarkeit
- Kapital 4: Zulassigkeitsprufung
- Kapitel 5: zusammenfassung der wichtigsten ergebinsse
Originally presented as the author's thesis (doctoral)--Universitt St. Gallen, 2009.
Keywords: International Criminal Court; Jurisdiction (International law); Criminal jurisdiction